Deformation mechanism of MWCNT/Ni composites under shear deformation: a molecular dynamics study - Jiajia Zuo; Yaxuan Hu; Binhe Wu; Rui Shu; Baipo Shu (Materials Research Express)
Multi-walled carbon nanotubes (MWCNTs) embedded in single-crystal and polycrystalline nickel were modeled by molecular dynamics simulations. Shear deformation was applied to the model perpendicular to the axial direction of the carbon nanotubes. In the case where single crystals are considered, the interfacial bonding between MWCNTs and nickel is weaker than the interaction force between nickel atoms. There is a difference in the deformation capacity between MWCNTs and the matrix, which leads to the concentration of stresses at the interface. The formation of defects near the interface and the debonding of the interface between MWCNT and the matrix cause material failure. In the polycrystalline model, MWCNT is considered to be located at grain boundaries or within the grain. The CNT/Ni interface and grain boundaries are both nucleation sites for dislocations and barriers to dislocation movement during deformation. The distribution of MWCNT in the matrix has an effect on the mechanical properties and deformation behavior of composites.